Changing of the spatial development means and institution in hungary after the change of regime - Krisztina Sóvágó; Valéria Jusztin (European Regional Science Association (ERSA), 2004)
Before 1990, regional development policy as a governmental function was of secondary importance. Although economic planning, control and management were based on sectoral principles, regional processes contributed towards an equilibrium in the sense that differences in social-economic development were decreasing among the various regions. This apparent contradiction is attributable to Hungary's economic structure. Before 1990, due to the lack of market and competition, the economic system basically gave support to and protected weaker regions at the expense of the strong ones. These tendencies hindered the dynamism of the economy while leading to the mitigation of regional imbalances. In the first half of the 1990s, spatial development activity in Hungary was of transitory nature. Partly because of the untested practice of spatial development management, institutions and mechanism, and partly because of the absence of a medium-level authority with appropriate powers, the issues that required intervention had to be handled by means of direct governmental instruments. The insufficiency of the available instruments, however, hindered the efficiency of individual interventions. The process of economic recession highlighted the need to create new spatial development instruments in order to manage growing regional disparities, the problems of depressed regions affected by serious social and economic crisis. The clearly unfavourable regional trends created the need for establishing a more pronounced regional policy with a new institutional system, decentralisation of decision-making, co-ordination of resources. Its basis was laid down in Act XXI of 1996 on Spatial Development and Planning. The law specifies the tasks and identifies the instruments and institutions of spatial development and planning. With the adoption of the Act, Hungary was the first among the accession countries to create a legal framework in conformity with EU spatial development requirements. A review of spatial processes and measures indicates that in the 1990s spatial development policy established its new network of instruments and institutions, primarily with a view to mitigating spatial disparities and it focused, in particular, on underdeveloped and depressed regions. Although this policy could reduce the unfavourable effects of market-based spatial differences in the economy, it could prevent new excessive depressed (crisis-ridden) regions from surfacing, nevertheless it failed to put a halt to these trends.
Keywords: 330